First description of the male of the easternmost Harpactea species, H. parthica (Araneae: Dysderidae) - Zamani, Alireza; Marusik, Yuri M.; Koponen, Seppo (Zootaxa, 2017)
Within Dysderidae, Harpactea Bristowe, 1939 (178 species) is second only to Dysdera Latreille, 1804 (264 species) in number of species (WSC 2016). Harpactea is distributed from Portugal (Helsdingen 2015) to eastern Iran (Brignoli 1980) and, although there are many publications dealing with the taxonomy of Harpactea, an inclusive revision of the genus has never been done. In a paper on the Dysderidae of the Caucasus Dunin (1992) provided a regional revision of Harpactea.